Perilaku Manajerial Kepala Sekolah Dalam Meningkatkan Kualitas Kerja Guru di MTS Al-Musthofa Tsani Rantau Badak Kec. Muara Papalik Kab. Tanjung Jabung Barat - Ridwan Ridwan; Muhlisin Muhlisin; Ahmad Ridwan; Muhammad Sanusi; Haidir Haidir (STIKes Ibnu Sina Ajibarang, 2023)
The principal is the person responsible for improving teacher performance at school. The purpose of this study was to determine the principal's leadership behavior in improving teacher performance at MTs Al Musthofa Sani Rantau Badak, Muara Papalik District. Research using a qualitative approach with data collection techniques of documentation, observation and interviews. The research subjects were school principals and teachers. This research shows that: (1) The formulation of the principal's policy in improving the ability of teachers at MTs Al Musthofa Sani Rantau Badak, Muara Papalik District, has made written and oral rules in accordance with the school's vision and mission by involving teachers, school objectives and school principals to formulate activities to improve teacher abilities. These results enable teachers to teach better so that students more easily understand lessons and can feel comfortable while at school and achieve a better quality of education; (2) The principal's program as a leader in improving the discipline of teachers at MTs Al Musthofa Sani Rantau Badak, Muara Papalik District by using good communication (not rude, direct supervision, not arrogant and authoritarian), compiling a KKG program, seminars and workshops with this program show encouraging results, teachers are more disciplined so they can complete their tasks well; (3) The principal's strategy as a leader in increasing the responsibilities of teachers at MTs Al Musthofa Sani Rantau Badak, Muara Papalik District by involving all teachers and providing direct examples and (4) The factors that influence the leadership of the principal in improving teacher performance are his desire to improve school performance so that he has better performance at the Acehnese and national level. This is the main factor that influences it along with other general factors, such as: the personal condition of the school principal, school organization, external environment.